Audio-Assisted Learning in the Gita Andap Nusantara Choir at the Nusantara Student Dormitory in Surabaya - klaudiana putri Jehadut (Jurnal Pendidikan Sendratasik, 2026)
The Gita Andap Nusantara Choir is an elective program organized by the Nusantara Student Dormitory in Surabaya, aimed at fostering interest and talent in the field of music, particularly in choral singing. From 2023 to the present, the Gita Andap Nusantara Choir in Surabaya has undergone significant changes, marked by the growing abilities and skills of its members. This study employs a qualitative approach. The research location is the Nusantara Student Dormitory in Surabaya, located at Jl. Jemur Andayani No. 1, Siwalankerto, Wonocolo District, Surabaya City. Data collection techniques include observation, interviews, and documentation. The results of the study indicate that audio-assisted learning is effective and efficient when used in choral music instruction. With this learning medium, members of the Gita Andap Nusantara Choir can access learning materials more freely, become more active, and develop their abilities. Audio media in choir instruction can help members of the Gita Andap Nusantara Choir master the material more quickly, saving time in the learning process.